Hubungan Antara Indeks Massa Tubuh dan Daya Tahan Kardiovaskular - Sandi Prayudho; Qorry Armen Gemael; Deden Akbar Izzuddin; Rayfal Fahmi Paturohman; Rizki (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the relationship between Body Mass Index (BMI) and cardiovascular endurance among students of the Sport Science Study Program at Singaperbangsa University, Karawang. The background of this study is based on the importance of cardiovascular fitness as an indicator of health and physical performance, as well as the increasing variability of nutritional status among students due to lifestyle changes. This study used a correlational design with purposive sampling, involving 30 students aged 18–25 years who met the inclusion criteria regarding health conditions and readiness to participate in fitness testing. Body Mass Index (BMI) was measured through height and weight assessments, while cardiovascular endurance was evaluated using a bleep test to obtain aerobic capacity scores. Descriptive results showed that the students' endurance levels were categorized as fair to good, with an average score of 8.43 ± 0.917. Meanwhile, the average BMI was 21.91 ± 3.28, categorized as normal, although the range indicates variations in nutritional status from underweight to overweight. Pearson correlation analysis revealed a significant positive relationship between BMI and cardiovascular endurance (r = 0.401; p = 0.031). This finding suggests that changes in BMI contribute to variations in students' endurance, particularly in the context of exercise science students who tend to have higher muscle mass, meaning that increased BMI may reflect greater muscle mass than fat mass. This study emphasizes that BMI remains relevant as a baseline indicator for assessing students' cardiovascular capacity, although its interpretation should be accompanied by more specific body composition measurements.